2020
DOI: 10.3389/fbioe.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

AgeGuess, a Methylomic Prediction Model for Human Ages

Abstract: Aging was a biological process under regulations from both inherited genetic factors and various molecular modifications within cells during the lifespan. Multiple studies demonstrated that the chronological age may be accurately predicted using the methylomic data. This study proposed a three-step feature selection algorithm AgeGuess for the age regression problem. AgeGuess selected 107 methylomic features as the gender-independent age biomarkers and the Support Vector Regressor (SVR) model using these biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The ridge regression (Ridge) evaluates a subset of features for their connections with the class labels ( Gao et al, 2020 ; Xu et al, 2020 ). Ridge provides a model-based trade-off between the fitting and complexity of the features by adding the L2 regularization to the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…The ridge regression (Ridge) evaluates a subset of features for their connections with the class labels ( Gao et al, 2020 ; Xu et al, 2020 ). Ridge provides a model-based trade-off between the fitting and complexity of the features by adding the L2 regularization to the regression model.…”
Section: Methodsmentioning
confidence: 99%
“…The parameter k denotes the number of selected features and is a common parameter in all the methods evaluated in this study. There is no fixed procedure in the literature for determining the optimum value of k, but in many research works [48][49][50][51] , it is set to 50 which seems to be satisfactory in many cases. However, we take k in a wider range from 10 and 90 to ensure a fairground for comparison.…”
Section: Datasetsmentioning
confidence: 99%
“…The last step of Crystall further refined the subset of selected features using the BackFS strategy [92]. The first two steps of Crystall eliminated features with small absolute values of the model coefficients, instead of the regression performance metric MAE.…”
Section: Crystall a Feature Selection Algorithm To Estimate Thementioning
confidence: 99%
“…The regression performance metric MAE is used to compare the features selected by Crystall-Step1 and Crystall. The previous studies demonstrated that the module BackFS performs very well on various feature selection problems, but its time complexity is very high [92]. So a wrapper is integrated as the second step of Crystall.…”
Section: E Regression Performance Comparison Of Feature Selection Almentioning
confidence: 99%